1985
DOI: 10.1093/jac/16.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recurrent genital herpes simplex infections with oral acyclovir

Abstract: A total of 113 patients with recurrent genital herpes were enrolled in a multicentre cross-over study. Two consecutive recurrences were treated with either oral acyclovir 200 mg or matching placebo five times daily for five days. Acyclovir significantly reduced the time to crusting and healing and the duration of new lesions and symptoms. Acyclovir was not found to have any clinically significant effect on the haematological or biochemical parameters measured, or to have caused adverse events and was well tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“…9,11 In all of the studies in which acyclovir treatment was patient initiated, the mean lesion healing time was reduced by approximately 1 to 2 days compared with placebo. 9,11,20 In the present study, the median lesion healing time was likewise reduced by approximately 1 day (4.8 days vs 6.0 days with placebo) in the acyclovir treatment group. Reichman et al 11 found that the duration of virus shedding in patients treated with acyclovir was reduced by a mean of 1.7 days below the placebo value of 3.9 days, which is in agreement with the 2-day median reduction shown in the present study.…”
Section: Commentsupporting
confidence: 58%
See 1 more Smart Citation
“…9,11 In all of the studies in which acyclovir treatment was patient initiated, the mean lesion healing time was reduced by approximately 1 to 2 days compared with placebo. 9,11,20 In the present study, the median lesion healing time was likewise reduced by approximately 1 day (4.8 days vs 6.0 days with placebo) in the acyclovir treatment group. Reichman et al 11 found that the duration of virus shedding in patients treated with acyclovir was reduced by a mean of 1.7 days below the placebo value of 3.9 days, which is in agreement with the 2-day median reduction shown in the present study.…”
Section: Commentsupporting
confidence: 58%
“…[9][10][11][12]20 In contrast to the present study, these clinical trials involved smaller numbers of patients treated with acyclovir (31 to 106 patients vs 506 patients in the present study), examined fewer efficacy parameters, analyzed and reported treatment differences in efficacy parameters in terms of means instead of medians, and were inconsistent or unclear with regard to time of initiation of treatment (which varied from "at the earliest sign of a recurrence" 9 to within 48 hours of signs and symptoms 10 ). In only 3 of the 5 clinical trials was treatment initiated by patients, as it was in our study.…”
Section: Commentmentioning
confidence: 99%
“…Dr. Goldberg's study suggested that early therapy was associated with a higher frequency of aborted episodes, although the differences between acyclovir and placebo recipients were not statistically significant. This effect has been shown in an additional study (5), while others have not demonstrated this (4).…”
Section: Acyclovir Prophylaxis For Herpes Simplex Virus Infectionmentioning
confidence: 71%
“…Another approach to patients with frequent recurrence is based on the method of treating individual attacks described by Forsbeck et al 31 Patients carry acyclovir tablets with them at all times and begin therapy at the start of the firstsymptom. Formaximum effect time should be spent establishing the first symptom and identifying its onset.…”
Section: Abortive Therapymentioning
confidence: 99%